Software para controle produtivo e reprodutivo de bovinos leiteiros na agricultura familiar - Carvalho, Alexandre de (2008)
CARVALHO, Alexandre. Software for productive and reproductive control of dairy bovines in family agriculture. Advisor: ANDRADE, Gustavo Augusto de. Co-advisor: REIS, José Cláudio. UNIFENAS: Alfenas, 2008 (Dissertation for a master s degree in Farm Production Systems). This paper intends to develop an information system that may help the producer in making decisions with basis on data about his herd, by means of keeping basic systematic animal records and the main indexes for productive and reproductive control of dairy cattle. A simple and intuitive operational interface was developed with the purpose of facilitating its use by persons with little practice with computers. The development model was based on prototyping, when several prototypes were created, tested and discarded. The final system is shown in this work.